Orchids of the Southern Cone (1830–2000) – Part III. Karl Friedrich Reiche’s Orchidaceae Chilensis and a commentary about Friedrich Wilhelm Ludwig Kraenzlin’s Orchidacearum Genera et Species (Vol. 2, Part I) - Ossenbach, Carlos (Lankesteriana: International Journal on Orchidology, 2023)
Karl Reiche (1860–1929), a German botanist, came to Chile in 1889 as a professor at the Lyceum in the city of Constitución. He was attracted by the country’s climate and its traditional friendliness to German immigrants. A few years later, in 1897, Federico Phillippi, Director of the Museo Nacional de Historia Natural, welcomed Reiche as the new Head of the Botanical Section, a position he held until 1910. During his 21 years in Chile, Reiche worked intensively on the Chilean flora and was a prolific writer. Besides six volumes of the Estudios críticos de la Flora de Chile (1896–1911), several editions of Reiche’s Plant Geography of Chile were published (1907, 1934–1937, 2013), a magnificent essay on Chiles’ Orchidaceae, Orchidaceae Chilensis (1910, reprint 2007), and several other minor works. On Reiche’s suggestion, The Museo Nacional engaged Friedrich Kraenzlin (1847–1934) to write a treatment of the orchids of the Southern Cone that was published in 1904 as the second volume of Orchidacearum Genera et Species, a work that was widely criticized by many botanists, beginning with Reiche himself.